Ninth International Congress and Nineteenth Annual Congress of Clinical Oncology - Makhdoumi, Yasha; Tabatabaeefar, Morteza (Reports of Radiotherapy and Oncology, 2025)
Abstract: The Ninth International Clinical Oncology Congress was held from January 29 to 31 at the Olympic Hotel in Tehran, Iran. Over the years, our goal has been to advance the scientific programs of our society and support research and development in various sectors. We strive to participate in these scientific programs, provide effective strategies, foster optimal interaction among researchers and clinicians, and offer resources to enhance scientific accountability. Additionally, we aim to create a suitable platform for informed policymaking in science and technology for youth, leveraging the facilities of organizations and scientific centers to elevate public understanding and achieve sustainable development in these fields. This year’s congress focused on three main themes. The first theme was “Oncology and Personalized Medicine”, which aims to tailor treatment based on each patient’s unique genetic makeup, marking a new era in oncologic care. The second theme was “Use of AI in Oncology”. This explored the role of artificial intelligence in transforming the landscape of oncology and cancer research. The third theme was “Ethics and Oncology”, which emphasized how ethical decisions in cancer care create a framework for balancing innovation with compassion. The target audience for this congress included radiation oncologists, medical physicists, radiotherapy technicians, radiobiologists, and oncology nurses. Dr. Yasha Makhdomi President of ISRO and ISCO Congress At the Ninth International Clinical Oncology Congress, we discussed the most important and recent advances in treatment options in the field of oncology. The primary goal of the congress was to enhance our understanding of oncology, which will hopefully pave the way for improving the healthcare services provided to our patients. We also saw this event as an opportunity to increase empathy and collaboration among our colleagues. Organizing this congress would not have been achievable without the assistance of the incredible people who supported us throughout the different phases of planning and implementation. We are grateful to all of these dear ones for their time and effort, and value their hard work. Dr. Morteza Tabatabaeifar, Scientific Chairperson